Language learning strategies of Arabic major students at Prince of Songkla Univerity, Pattani Campus, Thailand - Sideh, Ibrohem (Institute of Education, International Islamic University Malaysia, 2013)
This study aimed at investigating language learning strategies (LLS) employed by Prince of Songkla University (PSU) students majoring in Arabic language. Additionally, this study also attempted to determine the Arabic language proficiency (ALP) levels of the students, as well as to examine the relationship between the two variables (LLS use and ALP). Finally, it sought to explore whether there is any significant difference among students from different years of studies in their frequencies of using LLS in Arabic language learning. The research design used was quantitative, which utilizing survey outline as a method to collect the data. The population were the Arabic undergraduate students of all levels (year 1-4), with a total number of 123 students. Strategy Inventory for Language Learning (SILL) developed by Oxford (1990) and ALP questionnaires were used as instruments for this study. Result findings revealed that PSU students were familiar with all six LLS categories: memory, cognitive, compensation, metacognitive, affective, and social strategies, with a medium frequency use level of overall strategies. Among these six strategies, the most frequently used were metacognitive, social, and compensation strategies; whereas the least frequently used included cognitive, affective, and memory strategies. The result findings also showed a moderate level of Arabic language proficiency of PSU students. A positive correlation between the use of LLS and ALP was also found statistically significant. Furthermore, the results revealed a significant difference in the utilization of LLS among students of four different educational levels.